2018
DOI: 10.1111/ele.13162
|View full text |Cite
|
Sign up to set email alerts
|

Towards a multi‐trophic extension of metacommunity ecology

Abstract: Metacommunity theory provides an understanding of how spatial processes determine the structure and function of communities at local and regional scales. Although metacommunity theory has considered trophic dynamics in the past, it has been performed idiosyncratically with a wide selection of possible dynamics. Trophic metacommunity theory needs a synthesis of a few influential axis to simplify future predictions and tests. We propose an extension of metacommunity ecology that addresses these shortcomings by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
130
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(136 citation statements)
references
References 159 publications
(271 reference statements)
5
130
1
Order By: Relevance
“…Our results are more aligned with multi-trophic metacommunities that consider interspecific variation in dispersal rates ( i.e. Vellend et al 2014; Guzman et al 2019). Because the species in our communities have different dispersal rates, isolation was not only a process that increases stochasticity in the frequency of species arrival ( i.e.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our results are more aligned with multi-trophic metacommunities that consider interspecific variation in dispersal rates ( i.e. Vellend et al 2014; Guzman et al 2019). Because the species in our communities have different dispersal rates, isolation was not only a process that increases stochasticity in the frequency of species arrival ( i.e.…”
Section: Discussionsupporting
confidence: 74%
“…More importantly, the effects of fish and isolation are highly dependent on each other in ways that differ from those expected by classic metacommunity models ( e.g. Mouquet & Loreau 2003; Leibold et al 2004; Leibold & Chase 2018), but similar to what would be expected for multitrophic metacommunities with variable dispersal rates among species (Vellend et al 2014; Guzman et al 2019).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Empirical studies have found that the buffering capacity of dispersal depends on the stressor and the ecosystem metric (Thompson & Shurin ; Symons & Arnott ) and varies widely among studies (Eggers et al ; Lindo et al ; Thompson & Shurin ; Symons & Arnott ; de Boer et al ). Part of this complexity likely stems from environmental change and dispersal having differential effects on different groups of organisms (Voigt et al ; De Bie et al ; Guzman et al ). Consequently, the capacity of dispersal to mitigate effects of environmental change could vary among functional and trophic groups.…”
Section: Introductionmentioning
confidence: 99%